Jaroslav Ilnytskyi’s 50th birthday (Condensed Matter Physics, 2013)
On October 7, 2013 a renowned Ukrainian physicist working in the field of soft matter physics, a member of the Editorial Board of "Condensed Matter Physics", Leading Researcher of the Institute for Condensed Matter Physics, Doctor of Science in physics and mathematics Jaroslav Ilnytskyi celebrates his 50th birthday.